Clinical significance of hormonal receptor status of malignant ovarian tumors - Tkalia, I.G.; Vorobyova, L.I.; Svintsitsky, V.S.; Nespryadko, S.V.; Goncharuk, I.V.; Lukyanova, N.Y.; Chekhun, V.F. (Experimental Oncology, 2014)
Objectives: To study hormonal receptor status (HRS) of malignant ovarian tumors (MOT) and determine its clinical significance. Patients and Methods: Retrospective analysis of case histories of 284 patients with MOT of different genesis of I–IV stages was carried out; immunohistochemical study of paraffin-embedded tissues. The HRS for serous, mucinous ovarian cancer (OC) and sex cord-stromal tumors (SCST) was studied. The phenotype of tumors by HRS in patients with serous OC was determined; overall and relapse-free survival in these patients was evaluated depending on the tumor HRS. Results: Positive expression of ER has been registered in 66.4% of patients with serous OC, PR — in 63.4%, TR — in 53.0%; in patients with mucinous OC — 88.0; 84.0; 60.0%, respectively. Positive staining of cells of stroma-cellular tumors has been observed in 74.1% of patients for ER and 77.8% — for PR and TR. The highest number of patients with tumor phenotype ER+PR+TR+ has been observed in postmenopause — 52.4%, especially in late postmenopausal period — 39.0%. The lowest percentage of patients with mentioned phenotype has been marked in reproductive age — 20.7%. Most patients of reproductive period had phenotype of tumor ER-PR-TR- (35.1%), in late postmenopause this phenotype has been observed only in 16.2%. The patients with serous OC with the positive tumor HRS demonstrated the low indices of overall and relapse-free survival compared to the patients with receptor-negative tumors concerning all steroid hormones (р < 0.05). Conclusions: Positive HRS was registered in serous, mucinous OC and in SCST, high percentage of tumors with expression of all receptors of steroid hormones was observed at that. The highest frequency of tumors with positive HRS was recorded in patients with serous OC of late postmenopausal period. The patients with serous OC with receptor-positive tumor phenotype showed the rates of overall and relapse-free survival significantly lower compared to the patients with receptor-negative phenotype of OC. Positive HRS, the same as strong expression of TR in patients with serous OC, is a predictive factor of unfavorable course of tumor process. HRS of MOT can be regarded as the additional criterion for solution of a question concerning application of hormonal therapy as a component of complex treatment for the patients. Key Words: malignant ovarian tumors, serous ovarian cancer, hormonal receptor status, estrogen, progesterone, testosterone receptors, phenotype of tumor.